Evolve or perish! The Continued Development of Information and Knowledge Services in the UK Defence Science and Technology Laboratory - Davies, Dominic A.; Baron, Hannah M. (Qualitative and Quantitative Methods in Libraries, 2017)
Timely provision of the right information to inform decisions and support research within the Defence Science and Technology Laboratory (Dstl) ensures that the public purse is not wasted and, in extreme cases, saves lives.  Dstl provides Library and Information Services (LIS) through a centralised service model with a high reliance on staff that can embed themselves into the work of their user community.  The service model focuses on the provision of cost-effective resources and supports exploitation of the organisation‟s, and others‟, intellectual capital.  This model has been successfully developed over a decade and has stood the test of re-organisations and cost saving measures where many other LIS models in other organisations have failed.